Global spread of a Japan-originated Delta lineage of SARS-CoV-2 after the Tokyo Olympics is most likely unrelated to the Olympics - Shimura, T.; Kosaki, K. (Journal of Travel Medicine, 2022)
Participants of the 2021 Summer Olympics in Tokyo were required to adhere to strict health protocols, and there were no major local outbreaks within the separation bubbles. However, based on viral genomic data, we report that the Japan-specific Delta variants did spread out globally during or after the Olympics.